The Role of Political Parties in Providing Political Education Among Gen Z - Labolo, Muhadam (SEAN Institute, 2022)
This study aims to analyze the role played by political parties in providing political education to generation Z (Gen Z), which is the younger generation born between 1996 and 2012. Political education has an important role in forming a comprehensive and critical understanding of political processes. , democracy, and the rights and obligations of citizens. This study uses a qualitative research method with a descriptive approach. The results of the study show that the role of political parties in providing political education can be done by building political participation, encouraging critical thinking, mobilizing active participation, providing space for discussion, and building political awareness. The strategies for realizing this role include utilizing digital technology, building online communities, holding educational events, collaborating with youth communities, providing space for representatives of generation Z, and using issue-based campaigns.